Nile Delta Sedimentary Basin—A Big Data Guided Digital Petroleum Ecosystem - Nimmagadda, Shatri; Hanafy, Said; Reiners, Torsten (Springer, 2018)
Volumes of geological and geophysical (G & G) data sources exist in the Nile Delta basin, covering approximately 60,000 km2 in both onshore and offshore areas. Although several varieties of data continue to support the exploration and field development activities in the basin, the Big Data sources are largely unstructured, heterogeneous and multidimensional. Connecting various G & G events of onshore-transition-offshore zones and integrating them into a single repository is a complicated process. The authors proposed a holistic data warehousing and mining methodology that can support logical and physical data organization, easing the data integration process in the warehouse repository. In addition, an implementable framework, the Nile Delta Digital Petroleum Ecosystem (NDDPE) was articulated, assessing its usability and interoperability with associated data artefacts. The NDDPE can deliver Big Data guided digital ecosystem solutions that can minimize the risk of exploration.